Effectiveness of brief suicide management training programme for medical residents in Japan: a cluster randomized controlled trial. (June 2014) - Suzuki, Y.; Kato, T. A.; Sato, R.; Fujisawa, D.; Aoyama-Uehara, K.; Hashimoto, N.; Yonemoto, N.; Fukasawa, M.; Otsuka, K.
<x content-type="archive" xml:space="preserve">Abstract</x> Aims. To evaluate the effectiveness of a brief suicide management training programme for Japanese medical residents compared with the usual lecture on suicidality. Methods. In this multi-center, clustered randomized controlled trial, the intervention group attended a structured suicide management programme and the control group, the usual lecture on depression and suicidality. The primary outcome was the difference in residents' cumulative competency score to manage suicidal persons from baseline (T0) to 1 month after the intervention (T2), determined using the Suicide Intervention Response Inventory (SIRI-1) score, at individual level. Results. Analysis of 114 residents (intervention group n = 65, control group n = 49) assigned to two clusters in each group revealed no change in SIRI-1 score from T0 to T2 or immediately after the intervention (T1) between the two groups. As a secondary analysis, discrepancy in judgement between the participants and Japanese suicidologists was examined immediately after the intervention in the adjusted model, with a mean difference in score of 9.98 (95% confidence interval: 4.39–15.56; p = 0.001). Conclusions. The structured programme was not proven to improve competency in suicide management when measured by the SIRI-1 score. Further elaboration of the programme and valid measurement of its outcome would be needed to show the program's effectiveness.